STUDYING THE DEVELOPMENT OF THE CARDIAC SYSTEM IN SCHOOL-AGE CHILDREN - Mingishova Zarina Аkmaljon qizi (Journal Park Publishing, 2024)
The article describes the role of physical activity on the physiology of the cardiovascular system, that the measure of health is the level of activity of the main physiological systems and functional reserves of the body. Changes in heart rate under various loads and age characteristics.
Keywords: health, reaction, adaptation, cardiac system, transient insufficiency, parasympathetic nervous system, sympathetic nervous system.